Earth observation of ecosystem services - Alcaraz-Segura, Domingo (Earth observation of global changes., 2013)
"Offering a balanced review of differing approaches based on remote sensing methods to monitor ecosystem services related to biodiversity conservation, carbon and water cycles, and the energy balance of the terrestrial ecosystem, this book identifies the relevant issues and challenges of assessment, presents cutting-edge sensing techniques, uses globally implemented tools to quantify ecosystem functions, and provides numerous examples of successful monitoring programs. Covering recent developments undertaken on the global and national stage from earth observation satellite data, it includes valuable lessons and recommendations and novel ways to improve current global monitoring systems"--